EFEKTIVITAS PENGGUNAAN LKPD DALAM PEMBELAJARAN IPA TERHADAP PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK DI SDN 55/I SRIDADI - Novitasari; Faizati Umu Aimanah; Ulfa Ramadhani; Andre Pratama Sitepu; Risdalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is a dynamic and complex process that not only serves as a means of transferring knowledge, but also as a platform for developing skills, attitudes, and values to shape quality human resources. The Merdeka Curriculum is an innovative effort to provide flexibility for educators and students in the learning process, emphasizing the importance of character and competency development. One approach that supports the successful implementation of this curriculum is the use of Student Worksheets (LKPD). This study aims to examine the effectiveness of using LKPD in increasing student motivation and engagement in Science (IPA) learning in fourth-grade elementary school. The method used is qualitative research through observation, interviews, and documentation. The results of the study indicate that the active use of LKPD encourages student participation in discussions and experiments, as well as increasing their motivation and self-confidence. Teachers stated that LKPD facilitates the learning process and encourages students to think critically and creatively. These findings are reinforced by Abraham Maslow's hierarchy of needs theory, which explains that learning motivation will increase if students' basic needs up to self-actualization are met. LKPD designed in a contextual, gradual, and interactive manner has proven capable of meeting these needs. Thus, LKPD can serve as a stimulus in enhancing students' learning motivation while also functioning as an effective and enjoyable learning medium in supporting the implementation of the Merdeka Curriculum.